Low FODMAP: A preliminary strategy to reduce gastrointestinal distress in athletes - Lis, D. M.; Stellingwerff, T.; Kitic, C. M.; Fell, J. W.; Ahuja, K. D. K. (Medicine & Science in Sports & Exercise, 2018)
Introduction Gastrointestinal (GI) distress in endurance athletes is prevalent and detrimental to performance. Adverse GI symptomatology can be analogous with irritable bowel syndrome, where fermentable oligosaccharide, disaccharide, monosaccharide, and polyols (FODMAP) reduction has demonstrated efficacy. This study investigated the effects of low FODMAP (LFOD) diet on GI distress parameters in runners with a history of nonclinical exercise-associated GI symptoms.